Udder morphology and milk yield of East Friesian sheep - Makovicky, P.; Nagy, M.; Poráčová, J.; Konečná, M.; Margetín, M.; Milerski, M. (Diponegoro University, 2024)
Linear scores and measures of both udder and teat shape and size (thirteen traits) were assessed in 83 ewes of Improved Valachian breed (IV) and in crossbreds with East Friesian breed (EF 25% or EF 50%). At the same time, cistern measures and cross-section areas (fourteen traits) as well as milk yield and milkability were scanned using ultrasound technique or measured in the same individuals (130 measurements in each trait). Crossbreds with EF 50% had the largest udders in terms of depth, width, and height, as determined by either a nine-point linear score or exact measurements. Additionally, these crossbreds had teats that were more horizontally placed and the most appropriate udder attachment and shape. more horizontally and most appropriate udder attachment and shape. Ultrasound scans revealed that the areas of both the left and right udder cisterns scanned by ultrasound were the highest in EF 50% crosses. Overall cistern cross-section areas scanned from the side were 2934.6 mm2 in IV, 2932.6 mm2 in crosses of EF 25% and 3559.4 mm2 in crosses of EF 50% (P<0.05). Crossbreds of EF 50% had more appropriate machine milked milk and total milk yield (311.1 and 424.7 ml) than purebred IV (231.8 and 336.1 ml; P>0.05). On average, the proportion of machine-stripped milk was 33.2%, and non-significant influence of genotype was shown. Furthermore, all traits under study showed non significant differences between crosses of EF 25% and 50%.